DESIGN OF A 7-STORY HOTEL WITH A BASEMENT IN OXNARD, CA, USA - Khaidarova, Assemay; Satov, Serikbolsyn; Bolatkhanov, Iskander; Iskakova, Anel; Ismagulov, Nurbolat; Kaiyrkan, Assem (Nazarbayev University School of Engineering and Digital Sciences, 2024)
The following Capstone project displays a design from scratch proposed for a 7-story Hotel building with a Basement in Oxnard, California, US. Hereinafter, named as ‘élite’. The design process encompasses -four major engineering modules: Architectural/Structural, Geotechnical, Environmental, and Construction Management. Detailed calculations and design warranting structure’s vigorous stability of reinforced concrete frame in the presence of intense wind and seismic loads were conducted in the Structural part comprising 31% of the project. With a 34% share, the geotechnical component is crucial to the stability of the hotel in an earthquake-prone area because it focuses on foundation design and soil studies conducted in California. The strategies of handling Municipal Solid waste during the construction process and design life along with generation rates for the corresponding Hotel industry were revised in a detailed manner in the Environmental part of the report, correspondence of which to the project is 15%. Last but not least, the 20% of the project that is dedicated to Construction Management includes comprehensive planning, from project charter to risk management, to guarantee a smooth and efficient building process. The selection of Oxnard, a city with the required facilities and services, raises the hotel's allure to travelers. The hotel's proximity to Los Angeles and the natural wonders of the area make it an attractive business opportunity. Given Oxnard's natural characteristics as an earthquake zone and high wind speeds, the design of the climate-responsive architecture was the main concern. The project emphasizes high-quality materials and building techniques to create a firm, lifelong, and ecologically sustainable structure. The design procedures complies with the California Building Code and ASCE 7-10 standards.
Keywords: Type of access: Restricted